2000
DOI: 10.1093/brain/123.8.1722
|View full text |Cite
|
Sign up to set email alerts
|

Episodic memory in left temporal lobe epilepsy: a functional MRI study

Abstract: Left medial temporal lobe epilepsy (MTLE) is associated with verbal memory impairment usually related to hippocampal damage. We used functional MRI (fMRI) to investigate the patterns of functional activity in healthy volunteers and MTLE patients engaged in verbal episodic memory tasks to look for evidence of a reallocation of verbal memory in epileptic patients. fMRI data were collected from seven MTLE patients with left-sided hippocampal sclerosis and 10 healthy right-handed control subjects on a 3T scanner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
75
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(94 citation statements)
references
References 30 publications
13
75
0
6
Order By: Relevance
“…Similar results were obtained using event-related fMRI in left TLE (76). In another study, extensive activations were observed in left prefrontal regions during encoding and retrieval of verbal information in patients with left TLE, but not controls (77). Still other studies demonstrate a widespread decrease in functional activity in frontal and temporal regions during recall in TLE relative to controls (78,79).…”
Section: Fmrisupporting
confidence: 71%
“…Similar results were obtained using event-related fMRI in left TLE (76). In another study, extensive activations were observed in left prefrontal regions during encoding and retrieval of verbal information in patients with left TLE, but not controls (77). Still other studies demonstrate a widespread decrease in functional activity in frontal and temporal regions during recall in TLE relative to controls (78,79).…”
Section: Fmrisupporting
confidence: 71%
“…As the MFG is implicated in working memory, this finding may be a nonspecific effect of increased working memory demands as a result of generally compromised brain function, reflect compensation for greater demands on routine language function (in the way tasks perceived to be harder increase verbal working memory demands), or reflect compensation by working memory systems for disturbed hippocampal declarative memory function. [33][34][35] The interplay between the seizure focus and widespread regional networks is complex and pervasive. There are functional consequences of focal pathology that may have widespread effects on brain function.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with left temporal lobe epilepsy (TLE) show evidence of mesial temporal lobe hippocampal atrophy, as measured through magnetic resonance imaging (MRI) volumetry (16)(17)(18)(19)(20). Their deficits in explicit memory are well documented (21)(22)(23)(24)(25).…”
mentioning
confidence: 99%